The Influence of the Halal Label on Increasing Micro Small and Medium Enterprises (UMKM) in Ponca Rijang District - Ahmad Fadhil Kasim; Muhammad Rusdi; Sofyan B (MultiTech Publisher, 2024)
This study aims to determine the effect of the Halal Label on increasing Micro, Small and Medium Enterprises (MSMEs). With this research, it can be used as a reference in understanding and developing knowledge about the use of the Halal label on Micro, Small and Medium Enterprises (MSMEs) products. The research method used in this research is descriptive qualitative which aims to understand contextual conditions by leading to a detailed and in-depth portrait of natural environmental conditions, in relation to what actually happens outside based on what happens in the research area. Data sources in this study were obtained from interviews, documentation and literature review. The data analysis technique in this research is qualitative analysis taken from the Miles and Huberman model, namely, data reduction, data presentation, and conclusion drawing. By increasing income, capital, production, and the number of consumers, it can be concluded that the Halal label is very influential in increasing Micro, Small and Medium Enterprises (MSMEs) in Panca Rijang District.